Absence of nonlocal resistance in microstructures of PbTe quantum wells. Issue 1 (17th December 2012) - Kolwas, K. A.; Grabecki, G.; Trushkin, S.; Wróbel, J.; Aleszkiewicz, M.; Cywiński, Ł.; Dietl, T.; Springholz, G.; Bauer, G.
Abstract We report on experiments allowing to set an upper limit on the magnitude of the spin Hall effect and the conductance by edge channels in quantum wells of PbTe embedded between PbEuTe barriers. We reexamine previous data obtained for epitaxial microstructures of n‐type PbSe and PbTe, in which pronounced nonlocal effects and reproducible magnetoresistance oscillations were found. Here we show that these effects are brought about by a quasi‐periodic network of threading dislocations adjacent to the BaF2 substrate, which give rise to a p‐type interfacial layer and an associated parasitic parallel conductance. We then present results of transport measurements on microstructures of modulation doped PbTe/(Pb, Eu)Te:Bi heterostructures for which the influence of parasitic parallel conductance is minimized, and for which quantum Hall transport had been observed, on similar samples, previously. These structures are of H‐shaped geometry and they are patterned of 12 nm thick strained PbTe quantum wells embedded between Pb0.92Eu0.08Te barriers. The structures have different lateral sizes corresponding to both diffusive and ballistic electron transport in non‐equivalent L valleys. For these structures no nonlocal resistance is detected confirming that PbTe is a trivial insulator. The magnitude of spin Hall angle γ is estimated to be smaller than 0.02 for PbTe/PbEuTe microstructures in the diffusive regime.